(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Mine disposal is a critical facility that requires a stable slope design to ensure operational safety and the sustainability of mining activities. This study aims to analyze the stability of the planned mine disposal design at PT. XYZ, South Sumatra, and to evaluate the necessity of design improvement through a resloping approach. The initial disposal design applied a slope angle of 35°. The slope stability analysis results indicate that, at several locations, this slope angle produced factor of safety (FoS) values below the required stability criteria, classifying the disposal slopes as unstable. As a mitigation measure against slope failure risks, the slope geometry was modified by reducing the slope angle to 20°. The evaluation results demonstrate that the implementation of resloping significantly increased the FoS values to meet the disposal slope stability criteria. Therefore, a disposal slope design with a 20° inclination is recommended as a safer alternative for implementation at PT. XYZ to enhance operational safety and reduce the potential for slope failure.